Foxp3 Instability Helps tTregs Distinguish Self and Non-self - Zhang, Zhongmei; Zhou, Xuyu (Frontiers in Immunology, 2019)
Regulatory T cells (Tregs) are small subsets of CD4 T cells that play a central role in the controlling of immune tolerance. Tregs are either generated in the thymus (tTregs) or in the periphery (pTregs), both express the master transcription factor Foxp3. Stable expression of Foxp3 is important for the maintenance of Tregs identity and their suppressive function. Similar to T conventional cells, Tregs can recognize both self and non-self antigen, and TCR engagement leads to Treg activation and the generation of effector Tregs. Emerging shreds of evidence suggest Tregs are not always stable, even fully committed mature tTregs, can lose foxp3 expression and programming to effector-like T cells. In this review, we summarize recent finding in Treg instability and the intrinsic and extrinsic mechanism in controlling the Foxp3 expression. Final, we propose a new hypothesis that Foxp3 instability might help tTregs distinguish self and non-self antigens.